2011
DOI: 10.1155/2011/670508
|View full text |Cite
|
Sign up to set email alerts
|

New Low-Power Tristate Circuits in Positive Feedback Source-Coupled Logic

Abstract: Two new design techniques to implement tristate circuits in positive feedback source-coupled logic (PFSCL) have been proposed. The first one is a switch-based technique while the second is based on the concept of sleep transistor. Different tristate circuits based on both techniques have been developed and simulated using 0.18 μm CMOS technology parameters. A performance comparison indicates that the tristate PFSCL circuits based on sleep transistor technique are more power efficient and achieve the lowest pow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…It is found that all the proposed topologies consume half the power compared to the available switch based PFSCL tristate buffer [11] due to the fact that they all possess the provision of disabling the current flow in the high impedance state. In terms of propagation delay, it can be observed that all the topologies have almost equal delays since all of these possess similar loads and maintain the same bias current in the enabled state.…”
Section: Simulation Results and Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…It is found that all the proposed topologies consume half the power compared to the available switch based PFSCL tristate buffer [11] due to the fact that they all possess the provision of disabling the current flow in the high impedance state. In terms of propagation delay, it can be observed that all the topologies have almost equal delays since all of these possess similar loads and maintain the same bias current in the enabled state.…”
Section: Simulation Results and Discussionmentioning
confidence: 99%
“…An additional Enable signal is employed to achieve the desired functionality. In literature, two topologies to implement PFSCL tristate buffer are available [11]. These topologies use either a switch or a sleep transistor to attain a high impedance state.…”
Section: Available Pfscl Tristate Buffersmentioning
confidence: 99%
See 3 more Smart Citations